2000
DOI: 10.1179/096797800680910
|View full text |Cite
|
Sign up to set email alerts
|

New look at mathematical relationships among physical properties of brick products

Abstract: T he present paper extends previous findings already published where the relationships among total porosity, bulk density, compressive strength, and thermal conductivity were analysed. T he paper brings more accuracy into some original mathematical relationships and takes into account two additional physical properties (pore volume and the median pore radius). It has been found that the relationships between physical properties and a dose of any admixture added to brick clay could be better described using a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…When it is sought to decrease brick thermal conductivity by raising porosity, the ensuing reduction in mechanical strength needs to be taken into account, thus also making it of interest to understand how brick composition and microstructure influence mechanical strength [12,13]. This issue has been addressed in few studies, which report that the microstructures formed by small pores provide greater mechanical strength [14].…”
Section: Introductionmentioning
confidence: 99%
“…When it is sought to decrease brick thermal conductivity by raising porosity, the ensuing reduction in mechanical strength needs to be taken into account, thus also making it of interest to understand how brick composition and microstructure influence mechanical strength [12,13]. This issue has been addressed in few studies, which report that the microstructures formed by small pores provide greater mechanical strength [14].…”
Section: Introductionmentioning
confidence: 99%
“…The porosity of the fired clay body affects not only its thermal conductivity (Erker, 2002) but also other properties, such as water absorption (Kato et al, 2008), bulk density (Ten et al, 2010a), and compressive strength (Liu, 1997). Their relationships can be expressed using mathematical functions (Sˇveda, 2000b(Sˇveda, , 2006. For example, the relationship between porosity and the fired clay body thermal conductivity can be expressed using the exponential function.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no sign of the presence of calcite and dolomite phases in the presently analyzed three brick samples and presence of mullite and residual forms of quart and cristobite indicated that these a century old brick samples should have good mechanical and physico-sintering properties. It is considered that the mechanical strength of the ceramic bodies can attribute to the formation of mullite, residual quartz content and its particle size, and amount of glassy phases present in it [24]; [25].…”
Section: Figure2 Xrd Patterns Of Clay Brick-p1mentioning
confidence: 99%